Effects of electroconvulsive therapy on amygdala function in major depression – a longitudinal functional magnetic resonance imaging study. Issue 12 (11th April 2017) - Redlich, R.; Bürger, C.; Dohm, K.; Grotegerd, D.; Opel, N.; Zaremba, D.; Meinert, S.; Förster, K.; Repple, J.; Schnelle, R.; Wagenknecht, C.; Zavorotnyy, M.; et al.
Abstract : Background: Electroconvulsive therapy (ECT) is one of the most effective treatments for severe depression. However, little is known regarding brain functional processes mediating ECT effects. Method: In a non-randomized prospective study, functional magnetic resonance imaging data during the automatic processing of subliminally presented emotional faces were obtained twice, about 6 weeks apart, in patients with major depressive disorder (MDD) before and after treatment with ECT (ECT, n = 24). Additionally, a control sample of MDD patients treated solely with pharmacotherapy (MED, n = 23) and a healthy control sample (HC, n = 22) were obtained. Results: Before therapy, both patient groups equally showed elevated amygdala reactivity to sad faces compared with HC. After treatment, a decrease in amygdala activity to negative stimuli was discerned in both patient samples indicating a normalization of amygdala function, suggesting mechanisms potentially unspecific for ECT. Moreover, a decrease in amygdala activity to sad faces was associated with symptomatic improvements in the ECT sample ( r spearman = −0.48, p = 0.044), and by tendency also for the MED sample ( r spearman = −0.38, p = 0.098). However, we did not find any significant association between pre-treatment amygdala function to emotional stimuli and individual symptom improvement, neither for the ECT sample, nor for the MED sample. Conclusions: In sum, the present study provides first results regarding functional changes in emotion processing due to ECT treatment using a longitudinal design, thus validating and extending our knowledge gained from previous treatment studies. A limitation was that ECT patients received concurrent medication treatment.